Photography and videography department, Dhaka University, at Shahbagh Road, Bangladesh - MD. Shoeb-Al-Kadri (BRAC University, 2012)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture in Architecture, 2012.